An Exploration of the Development of Melanoma ICI Resistance and Prevention and Treatment Strategies Based on the “Zheng-Xie” Theory - Zhang, Zicheng; Wang, Liwen; Tong, Danlei (Journal of Contemporary Medical Practice, 2026)
Immune checkpoint inhibitors (ICIs) are currently the primary treatment for melanoma, and resistance to ICIs is a major factor leading to treatment failure, recurrence, and metastasis in melanoma. The development of melanoma is closely related to the Traditional Chinese Medicine (TCM) theory of “Zheng and Xie”: deficiency of Zheng Qi is the foundation of melanoma onset; the accumulation of Xie is a trigger for its progression; and the combination of Zheng deficiency and Xie accumulation promotes the progression of melanoma. The pathological state of “deficiency of Zheng Qi and accumulation of Xie” creates conditions for the development of ICI resistance. The prevention and treatment of ICI resistance in melanoma using Traditional Chinese Medicine (TCM) should focus on two aspects: strengthening Zheng Qi and consolidating the foundation to address the “deficiency state,” and expelling Xie and clearing the source to address the “Xie state.” By restoring the balance between Zheng and Xie and implementing comprehensive, full-process treatment management, this approach provides new insights for the prevention and treatment of ICI resistance in melanoma using TCM.